Cultivation-Assisted Genome of Candidatus Fukatsuia symbiotica; the Enigmatic "X-Type" Symbiont of Aphids. (14th November 2019) - Patel, Vilas; Chevignon, Germain; Manzano-Marín, Alejandro; Brandt, Jayce W; Strand, Michael R; Russell, Jacob A; Oliver, Kerry M
Abstract: Heritable symbionts are common in terrestrial arthropods and often provide beneficial services to hosts. Unlike obligate, nutritional symbionts that largely persist under strict host control within specialized host cells, heritable facultative symbionts exhibit large variation in within-host lifestyles and services rendered with many retaining the capacity to transition among roles. One enigmatic symbiont, Candidatus Fukatsuia symbiotica, frequently infects aphids with reported roles ranging from pathogen, defensive symbiont, mutualism exploiter, and nutritional co-obligate symbiont. Here, we used an in vitro culture-assisted protocol to sequence the genome of a facultative strain of Fukatsuia from pea aphids ( Acyrthosiphon pisum ). Phylogenetic and genomic comparisons indicate that Fukatsuia is an aerobic heterotroph, which together with Regiella insecticola and Hamiltonella defensa form a clade of heritable facultative symbionts within the Yersiniaceae (Enterobacteriales). These three heritable facultative symbionts largely share overlapping inventories of genes associated with housekeeping functions, metabolism, and nutrient acquisition, while varying in complements of mobile DNA. One unusual feature of Fukatsuia is its strong tendency to occur as a coinfection with H. defensa. However, the overall similarity of gene inventories among aphid heritable facultative symbionts suggests that metabolic complementarity is not the basis for coinfection, unless playing out on a H. defensa strain-specific basis. We also compared the pea aphid Fukatsuia with a strain from the aphid Cinara confinis (Lachninae) where it is reported to have transitioned to co-obligate status to support decaying Buchnera function. Overall, the two genomes are very similar with no clear genomic signatures consistent with such a transition, which suggests co-obligate status in C. confinis was a recent event.